1999
DOI: 10.1097/00003246-199911000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia after coronary bypass surgery modeled by resistance to oxygen diffusion

Abstract: In cardiac patients requiring supplementary oxygen, the respiratory abnormality could, in our model, be best described by an increased Rdiff, not by an increased shunt value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 8 publications
2
44
0
Order By: Relevance
“…[1][2][3][4][5] Through univariate analysis, the risk factors were as follows: preoperative hypertension, preoperative diabetes, preoperative chronic pulmonary diseases, preoperative smoking, preoperative acute myocardial infarction, preoperative ventricular aneurysm, preoperative LVEF, preoperative LVEDD, preoperative PaO2, number of bypass graftings, the duration of cardiopulmonary bypass and aortic cross-clamp, and intraoperative total liquid volume. Furthermore, through logistic regression, the independent risk factors of postoperative hypoxemia following CABG were as follows: preoperative chronic pulmonary diseases, preoperative acute myocardial infarction, and preoperative diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Through univariate analysis, the risk factors were as follows: preoperative hypertension, preoperative diabetes, preoperative chronic pulmonary diseases, preoperative smoking, preoperative acute myocardial infarction, preoperative ventricular aneurysm, preoperative LVEF, preoperative LVEDD, preoperative PaO2, number of bypass graftings, the duration of cardiopulmonary bypass and aortic cross-clamp, and intraoperative total liquid volume. Furthermore, through logistic regression, the independent risk factors of postoperative hypoxemia following CABG were as follows: preoperative chronic pulmonary diseases, preoperative acute myocardial infarction, and preoperative diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports revealed that many factors and the interaction of these factors leads to postoperative hypoxemia following CABG. [1][2][3] In this study, the pre-, intra-, and post-operative materials in patients with coronary artery disease who had CABG performed on them from March 2004 to March 2008 were collected and analyzed retrospectively. The relative risk factors were tested through descriptive analysis and logistic regression, the independent high risk factors of postoperative hypoxemia were obtained, and the aim is to prevent and treat postoperative hypoxemia after CABG.…”
mentioning
confidence: 99%
“…This question has, and continues to be, addressed by a series of clinical PhD projects [29,30], and is not therefore the focus of this dissertation. To date, these have focused upon the post-operative effects of surgical interventions on gas exchange and the time course of changes thereafter [31][32][33][34][35]. The major finding of these studies, from the perspective of gas exchange, has been the peak in gas exchange abnormalities seen in the late post operative period, i.e.…”
Section: Alpe -Systems Development and Clinical Applicationmentioning
confidence: 99%
“…These single-parameter descriptions are insufficient, being unable to describe shunt and _ V= _ Q matching or to simulate changes in arterial oxygenation on varying FIO 2 [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%